Proving communal warfare among hunter‐gatherers: The quasi‐rousseauan error. Issue 3 (6th May 2015) - Gat, Azar
<x xml:space="preserve">Abstract</x> Was human fighting always there, as old as our species? Or is it a late cultural invention, emerging after the transition to agriculture and the rise of the state, which began, respectively, only around ten thousand and five thousand years ago? Viewed against the life span of our species, Homo sapiens, stretching back 150, 000–200, 000 years, let alone the roughly two million years of our genus Homo, this is the tip of the iceberg. We now have a temporal frame and plenty of empirical evidence for the "state of nature" that Thomas Hobbes and Jean‐Jacque Rousseau discussed in the abstract and described in diametrically opposed terms. All human populations during the Pleistocene, until about 12, 000 years ago, were hunter‐gatherers, or foragers, of the simple, mobile sort that lacked accumulated resources. Studying such human populations that survived until recently or still survive in remote corners of the world, anthropology should have been uniquely positioned to answer the question of aboriginal human fighting or lack thereof. Yet access to, and the interpretation of, that information has been intrinsically problematic. The main problem has been the "contact paradox." Prestate societies have no written records of their own. Therefore, documenting them requires contact with literate state societies that necessarily affects the former and potentially changes their behavior, including fighting.